Examining risk and risk perception on LSD and MDMA in online marketplaces - Bada, Maria (Journal of crime and justice, 2024)
The anonymity provided in underground forums has led to the growth of illicit substance drug markets. Online markets seem to be safer for drug transactions, with reduced risks of being arrested. However, criminals seem to be conscious of the risks of keeping a dark web market user friendly. This study investigates both surface and dark web forums, focusing on online underground markets. This study aims to: a) investigate the ways risk is perceived among members and vendors of underground forums throughout stages of transactions and b) identify risk avoidance practices utilised within these online underground markets. We hypothesise that the discourse in these forums focuses on the risks of detection, both offline and in cyberspace, as well as relevant techniques for reducing such risks. Our findings indicate discourse on techniques and strategies for reducing the risk of detection and arrest. In addition, our findings highlight that decision-making with drug use is highly individualised and should be based on some research of the effects and benefits of each drug. These findings provide useful insights and can inform practices in policing, leading to the development of intervention approaches aiming to interrupt online underground markets.